VALIDATION OF THERMOCHEMISTRY SUPPLEMENT BOOK BASED PROBLEM SOLVING TO TRAIN STUDENTS METACOGNITIVE SKILLS - Nuning Sabila Khoiroh; Utiya Azizah (JCER (Journal of Chemistry Education Research), 2021)
This research aims to know validity of thermochemistry suplement book based problem solving to train students metacognitive skills includes the content and construct. Content validity includes the suitability of the material and questions. Construct validity includes presentation and readability techniques. Problem solving model has 4 steps, that are understanding the problem, devising a plan, carrying out the plan, and lock back. Metacognitive skills consist of 3 components, namely planning, monitoring, and evaluating. The type of research used is the Research and Development (R&D) from Sugiyono. The supplement book was assessed by 3 experts in the field of chemical education using a validation instrument. The results showed that a chemical supplement book based on problem solving to train students' metacognitive skills on thermochemical material was very good with a score of 91.6% in content validation and 84.9% in construct validation.